Implementation Of The 2024 Women's Economic Empowerment Program in West Sumatra Province - Fitri, Annisa; Pertiwi, Indah; Mulia, Rizki Afri (Adabi : Journal of Public Administration and Business, 2025)
This study aims to analyze the implementation of the 2024 Women's Economic Empowerment Program organized by the Office of Women's Empowerment, Child Protection, Population Control, and Family Planning (DP3AP2KB) of West Sumatra Province in order to support the achievement of the Sustainable Development Goals (SDGs), particularly SDG 1 (poverty alleviation) and SDG 5 (gender equality). This study used a qualitative approach with descriptive methods. Data collection techniques included interviews, observations, and documentation studies. Data analysis was conducted using the Miles and Huberman interactive model. The results indicate that the empowerment program is implemented through three main forms: the PEKKA Program, the Women's Economic Empowerment Program, and the Women's Leadership Strengthening Program. However, the program's implementation remains hampered by several significant issues, such as suboptimal communication between relevant parties, limited available resources, low program implementer capacity, and an inflexible bureaucratic structure. In addition, external factors also hinder women's participation, such as lack of family support, unfavorable geographic conditions, and prevailing socio-cultural values. To address these obstacles, the DP3AP2KB has implemented several strategies, including a community-based approach, collaboration with various sectors, and the provision of follow-up training and post-program support. The findings of this study indicate that although program implementation has not yet reached its optimal level, the improvement efforts that have been made demonstrate positive progress in promoting women's economic independence at the local level. This study recommends strengthening coordination between various parties, increasing human resource (HR) capacity, and developing an accurate data-based monitoring system to increase the program's effectiveness and sustainability in the future.